Proyecto de Inversión para la Implementación de un Parque Recreacional en la Ciudad de Cariamanga - Jiménez Molina, Johanna del Cisne (2017)
The practice of sport and recreation is important as it helps the harmonious and integral development of human beings, so the idea arises of carrying out an investment project for the implementation of a recreational park in the city of Cariamanga that accommodates The urban families so that they can carry out recreational and physical activities in their free time providing them with an adequate infrastructure and tools for a healthy fun, and in this way contribute to the social and sports integration. The objective of the present investigation is to determine the feasibility of the recreational park based on the market study, technical study, administrative study, financial study and financial evaluation. The methods used were the inductive method that was used to know the tastes and preferences of the study population about the research, the deductive method was used to analyze the competition as well used the techniques of the interview that was performed to Mr. José Miguel Reátegui to determine the existing offer, the survey that was applied to the urban families of the cantaloulos to know their opinions about the project and the direct observation that allowed to know how the only public park that exists in the canton In the results a survey was applied both to the plaintiffs and offerers of the Canton to determine the acceptance of the service in the market. - 6 - Within the discussion the market study was carried out where a potential demand of 102,138 was established; An effective demand of 76,654; And an unsatisfied demand of 65,855 was subsequently established the marketing plan, determination of price, place and promotion of the service. The technical study detailed the size and location of the plant; In the administrative study, the constitution, organization and manuals of functions of the company and its collaborators were determined. The financial study indicates the investment required to implement the project, which is $ 114.363,19 dollars, of which $ 64.363,19 corresponding to 56,28% of the investment will be financed by each shareholder and 43,72% corresponding to $ 50,000 , 00 will be financed through the Banecuador bank with an interest rate of 9.76%. The financial evaluation was carried out. The following indicators were analyzed, giving us the following values: Net Present Value (VAN) of $ 6.454,08; Internal Rate of Return (IRR) of 19.09% Profit ratio Cost of 1.70 which means that for every dollar invested a profit of 0.70 cents will be obtained; Period of Capital Recovery is 4 years, 1 month and 13 days; Sensitivity Analysis indicates that the project supports a cost increase of 34.84% and that revenue can be reduced to 20,33% in sales. Finally, the conclusions, recommendations, bibliography consulted and the respective annexes are reached. - 7 - c. INTRODUCCIÓN Con el presente “PROYECTO DE INVERSIÓN PARA LA IMPLEMENTACIÓN DE UN PARQUE RECREACIONAL EN LA CIUDAD DE CARIAMANGA” se pretende contribuir al mejoramiento de las condiciones socio-económicas de la ciudad de Cariamanga. El emprendimiento hoy en día es de gran importancia porque conlleva a solucionar una serie de problemas relacionados con la baja productividad o prestación de servicios, escasos desarrollos empresariales, desempleo y pobreza de un país o ciudad. En la ciudad de Cariamanga no existe un parque recreacional que brinde los servicios necesarios en donde las familias puedan acudir para realizar una actividad recreativa ya que tradicionalmente los parques son utilizados por la sociedad para realizar actividades de distracción, entretenimiento y salir de la rutina diaria. Este servicio está orientado a cubrir las expectativas de la recreación familiar dentro de la ciudad de Cariamanga de una forma completa en todos sus sentidos y así mismo que sea asequible a la economía de la familia promedio de nuestra sociedad. El presente proyecto está estructurado de la siguiente manera: En la primera parte del presente trabajo encontramos el título de nuestro proyecto denominado: